Hubungan Kepercayaan Diri dengan Komunikasi Interpersonal - Restu Novi Andini; Ratna Widiastuti; Moch Johan Pratama (ALIBKIN (Jurnal Bimbingan Konseling), 2019)
The problem in this research is the relationship of low interpersonal cummunication. The purpose of this research was to determine the relationship between self-confidence and interpersonal communication of the students. The research method is quantitative. The sample is 42 students taken by simple random sampling technique. The technique’s of collecting data are a scale of confidence and interpersonal communication. The results showed that there was a positive and significant relationship between self-confidence and student interpersonal communication indicated by the correlation value r count = 0.409 r table = 0.304 at the significance level of α = 0.05 (p ≤ 0.05), then Ho was rejected and Ha was accepted. The conclusion of this research is that there is a positive and significant relationship between self-confidence and interpersonal communication in the tenth grade of Public High School 15 Bandar Lampung in 2018/2019, means that the higher the student's confidence, the higher interpersonal communication skills of students.Masalah dalam penelitian ini adalah hubungan komunikasi interpersonal rendah. Tujuan penelitian ini adalah untuk mengetahui hubungan antara kepercayaan diri dengan komunikasi interpersonal siswa. Metode penelitian bersifat kuantitatif. Sampel berjumlah 42 siswa yang diambil dengan teknik simple random sampling. Teknik pengumpulan data menggunakan skala kepercayaan diri dan komunikasi interpersonal. Hasil penelitian menunjukkan terdapat hubungan yang positif dan signifikan antara kepercayaan diri dengtan komunikasi interpersonal siswa yang ditunjukkan dengan nilai korelasi rhitung = 0,409 rtabel = 0,304 pada taraf sigifikansi α = 0,05 (p ≤ 0,05), maka Ho ditolak dan Ha diterima. Kesimpulan hasil penelitian ini adalah terdapat hubungan positif dan signifikan antara kepercayaan diri dengan komunikasi interpersonal siswa kelas X SMA Negeri 15 Bandar Lampung Tahun Ajaran 2018/2019, artinya semakin tinggi kepercayaan diri siswa maka akan semakin tinggi pula kemampuan komunikasi interpersonal siswa.Kata kunci: bimbingan konseling, kepercayaan diri, komunikasi interpersonal